Possible Involvement of a Mitochondrial Translation Initiation Factor 3 Variant Causing Decreased mRNA Levels in Parkinson's Disease. (1st June 2010) - Anvret, Anna; Ran, Caroline; Westerlund, Marie; Thelander, Ann-Christin; Sydow, Olof; Lind, Charlotta; Håkansson, Anna; Nissbrandt, Hans; Galter, Dagmar; Belin, Andrea Carmine
Abstract : Genes important for mitochondrial function have been implicated in Parkinson's disease (PD). Mitochondrial translation initiation factor 3 (MTIF3) is a nuclear encoded protein required for the initiation of complex formation on mitochondrial ribosomes. Dysfunction of MTIF3 may impair mitochondrial function and dopamine neurons appear to be particularly vulnerable to oxidative stress, which may relate to their degeneration in PD. An association was recently reported between the synonymous rs7669(C>T) in MTIF3 and PD in a German case-control material. We investigated rs7669 in a Swedish Parkinson case-control material. The study revealed no significant association of the individual genotypes or alleles with PD. When comparing the combined TT/CT-genotypes versus the CC-genotype, we observed a significant association (P = .0473 ) with PD. We also demonstrated that the TT-genotype causes a significant decrease in MTIF3 mRNA expression compared to the CC-genotype (P = .0163 ). Our findings support the hypothesis that MTIF3 may be involved in the etiology of PD.